Integrating Local Cultural Values ​​in Mathematics Learning: A Case Study of Ethnomathematics in Traditional Games - Nuriman Widiyasono; Ahmad Faisal; Nurul Aina Lestari (Gema Cendekia Institute, 2026)
Integrating local cultural values through an ethnomathematics approach in mathematics learning is believed to enhance students’ critical thinking skills and conceptual understanding. This study aims to analyze the implementation of ethnomathematics in traditional games at junior high schools in Indonesia and evaluate its contribution to mathematical comprehension. The study employed a qualitative case study design, collecting data via participatory observation, interviews with teachers and students, and documentation of learning activities. Data were analyzed using content analysis and narrative synthesis to identify learning patterns and links to ethnomathematics theory. Results indicate that integrating traditional games into mathematics learning significantly improves problem-solving skills enhances student motivation, and facilitates understanding of geometry, numbers, and logical strategies. Furthermore, the cultural values embedded in traditional games strengthen students’ cultural identity while increasing mathematics’ relevance in daily life. In conclusion, integrating ethnomathematics through traditional games is an effective strategy for meaningful and contextual mathematics learning. The study recommends curriculum development based on ethnomathematics at the junior high school level and further research to assess the long-term impact on student academic performance.